Case report: A novel variant (H49N) in Myelin Protein Zero gene is responsible for a patient with Charcot–Marie–Tooth disease - Cao, Gao-Hui; Zhao, Mei-Fang; Dong, Yi; Fan, Liang-Liang; Liu, Yi-Hui; Deng, Yao; Tang, Lu-Lu (Frontiers in Neurology, 2024)
This report presents a case of Charcot–Marie–Tooth dominant intermediate D (CMTDID), a rare subtype of Charcot–Marie–Tooth disease, in a 52 years-old male patient. The patient exhibited mobility impairment, foot abnormalities (pes cavus), and calf muscle atrophy. Whole exome sequencing and Sanger sequencing suggested that a novel variant (NM_000530.8, c.145C>A/p.His49Asn) of MPZ may be the genetic lesion in the patient. The bioinformatic program predicted that the new variant (p.His49Asn), located at an evolutionarily conserved site of MPZ, was neutral. Our study expands the variant spectrum of MPZ and the number of identified CMTDID patients, contributing to a better understanding of the relationship between MPZ and CMTDID.